PENENTUAN JUMLAH PESANAN EKONOMIS PERSEDIAAN VAKSIN MENINGITIS MENVEO PADA KANTOR KESEHATAN PELABUHAN (KKP) KELAS II SAMARINDA - -, Nurhidayati - (EKONOMIA, 2015)
This research aims to know the number of orders that are economical on The Kantor Kesehatan Pelabuhan (KKP) Kelas II Samarinda for Menveo Meningitis Vaccine and also to know the magnitude of the economic order quantity of Menveo meningitis vaccine for every time the frequency reservations.Analysis tool used is a model of Economic Order Quantity (EOQ) data research result such as booking fees, storage fees, rates and Menveo meningitis vaccine usage amount on The Kantor Kesehatan Pelabuhan (KKP) Kelas II Samarinda.The result of the analysis conducted in this study shows that when The Kantor Kesehatan Pelabuhan (KKP) Kelas II Samarinda undertake activities booking supplies vaccine Menveo meningitis in the number 14.000 vial with a frequency of orders by as much as 1 time in a year then raises the total cost of the inventory for a year of Rp 5.874.000,00.Result of calculation by using The EOQ model by means of the formula showed that the amount of vaccine Menveo meningitis supply economically at The Kantor Kesehatan Pelabuhan (KKP) Kelas II Samarinda, which is 11 times in a year with a number of reservations 1.297 vial each time a message is to use for 33 days. As for the time of rebooking is at a time when supplies of the vaccine in The KKP Kelas II Samarinda is at number 2.800 vial with grace time booking for 60 days.The total cost of the inventory during the year issued by The Kantor Kesehatan Pelabuhan (KKP) Kelas II Samarinda, which is about Rp 5.874.000,00 looks much different from the total cost of the inventory by using The EOQ model (formula), which amounted to Rp 1.079.259,02 per year. The cost of inventories using this model will be able to save the cost of inventories amounting to Rp 4.794.740,98 (Rp 5.874.000,00 - Rp 1.079.259,02). Or with the way the table it even Rp 1.079.454,54 per year. The cost of inventories using this model will be able to save the cost of inventories amounting to Rp 4.794.545,46 (Rp 5.874.000,00 - Rp 1.079.454,54).The difference between the cost of inventories by using a calculation formula (Rp 1.079.259,02) and the costs of supplies used table (Rp 1.079.454,55) it even Rp 195,53.